The Effectiveness of Uganda’s Legal Framework in Addressing Medical Malpractices - Milly Namukwaya (Uganda Christian University, 2025)
Medical malpractice , also known as medical negligence takes the form that a medical practitioner breaches the duty owed by him/her to the patient in attention. The litigation surrounding it is growing too, inclusive in the developing countries like Uganda. Day by day, accidents are inevitable and this can happen in the medical field; medical practitioner can be victims of the same, however, in some instances where the practitioner is responsible because of their actions or omission these laws come in to hold the practitioner liable. This, is a challenge, yet, culminating over time and reported increase is seemingly taking its centre stage. It cannot go ignored, that is why the study unfolding aims to address the Ugandan legal frame work on medical malpractice considering how effective this framework both domestic and international ratified laws have been effective, the causes of medical malpractice in Uganda , the responsiveness to medical malpractice and it will conclude with the findings and recommendations in regards to the matter at hand.
THESIS